The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.neuron.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic TrkC and Presynaptic PTPσ Function as a Bidirectional Excitatory Synaptic Organizing Complex

Abstract: SUMMARY Neurotrophin receptor tyrosine kinases (Trks) have well-defined trophic roles in nervous system development through kinase activation by neurotrophins. Yet Trks have typical cell-adhesion domains and express non-catalytic isoforms suggesting additional functions. Here we discovered non-catalytic TrkC in an unbiased hippocampal neuron-fibroblast coculture screen for proteins that trigger differentiation of neurotransmitter release sites in axons. All TrkC isoforms, but not TrkA or TrkB, function directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
269
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(281 citation statements)
references
References 54 publications
10
269
1
1
Order By: Relevance
“…Recent studies have established that a host of neuronal transmembrane proteins containing LRR domains play important roles in synapse development, although the precise functions of these proteins are only slowly being uncovered (3,13,17,20,(25)(26)(27). Six Slitrk family members (Slitrk1-6) share similar domain organizations and have been shown to regulate neurite outgrowth in Pheochromocytoma Cell Line 12 (PC12) cells (5,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have established that a host of neuronal transmembrane proteins containing LRR domains play important roles in synapse development, although the precise functions of these proteins are only slowly being uncovered (3,13,17,20,(25)(26)(27). Six Slitrk family members (Slitrk1-6) share similar domain organizations and have been shown to regulate neurite outgrowth in Pheochromocytoma Cell Line 12 (PC12) cells (5,28).…”
Section: Discussionmentioning
confidence: 99%
“…LAR-RPTP family members are evolutionarily conserved and are functionally required for axon guidance and synapse formation (15). Recent studies have shown that netrin-G ligand-3 (NGL-3), neurotrophin receptor tyrosine kinase C (TrkC), and IL-1 receptor accessory protein-like 1 (IL1RAPL1) bind to all three LAR-RPTP family members or distinct members of the family; however, the functional significance of these multifaceted interactions remains elusive (16)(17)(18).…”
mentioning
confidence: 99%
“…A systematic bioinformatics study has shown that extracellular LRR domain-containing proteins have greatly expanded in mammals (135 in mouse, 139 in human) compared with worms (29 extracellular LRR proteins) and flies (66 extracellular LRR proteins) (Dolan et al, 2007). The ligands of these extracellular LRR proteins remain largely unknown, although the process of ligand identification has recently accelerated (de Wit et al, 2009;Ko et al, 2009;Siddiqui et al, 2010;Takahashi et al, 2011;Woo et al, 2009). Mounting evidence from invertebrate systems shows that extracellular LRR proteins control key phases of neuron development and neural circuit formation including axon guidance, target-cell recognition, and synapse formation.…”
Section: Leucine-rich Repeats (Lrrs)mentioning
confidence: 99%
“…Inhibitory synapse formation (Slitrk3) (Takahashi et al, 2012) TrkC PTPσ (in vitro) Excitatory synapse formation (Takahashi et al, 2011…”
Section: Slit and Trk-like Familymentioning
confidence: 99%
See 1 more Smart Citation